ANALISIS IMPLEMENTASI KEBIJAKAN PENCEGAHAN DAN PENGENDALIAN HIV/AIDS: MENUJU PENCAPAIAN TARGET ”THREE ZERO” DI WILAYAH KABUPATEN CIREBON - Melati, Puji; Awaludin (Journal of Health Service Management, 2026)
Background: HIV/AIDS remains a major public health challenge in Indonesia, particularly in regions where new cases continue to increase. Cirebon Regency is one of the high-vulnerability areas, reporting 464 new HIV cases in 2024, predominantly among men who have sex with men (MSM). Local government efforts to achieve the global Three Zero targets zero new HIV infections, zero AIDS-related deaths, and zero stigma and discrimination require critical examination to assess policy effectiveness and alignment. Objective: This study aimed to analyze the implementation of HIV/AIDS prevention and control policies in Cirebon Regency, identify supporting and inhibiting factors in policy implementation, and assess the relevance of local policies to achieving the Three Zero targets. Methods: This study employed a qualitative descriptive policy analysis approach. Primary data were collected through in-depth interviews and limited observation involving four key informants: the Head of the Disease Prevention and Control Section of the Cirebon District Health Office, the HIV Program Coordinator at the District Health Office, the HIV Program Officer at Kalimaro Community Health Center, and a representative of a non-governmental organization supporting people living with HIV (PLHIV). Secondary data were obtained from policy documents and official program reports, including the HIV/AIDS Information System (SIHA), and were used solely to provide contextual information on program coverage and service gaps. The study did not apply a mixed-methods design. Data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation Results: The findings indicate that HIV/AIDS policy implementation in Cirebon Regency has not yet fully aligned with the Three Zero targets. Major challenges include the absence of a specific regional regulation on HIV/AIDS, limited intersectoral coordination, and persistent social stigma toward PLHIV. Antiretroviral therapy (ARV) coverage reached 80.7%, remaining below the global target of 95%. Conclusions: Strengthening regional regulations, expanding community-based education, and enhancing cross-sector collaboration are essential to accelerate progress toward achieving the Three Zero targets in Cirebon Regency.